Optimalisasi Perkembangan Anak Prasekolah melalui Tidur Sehat, Omega 3, dan Stimulasi Sesuai Usia (TOSS) - Eka Wahyuningrum; Andrea Putri Sekar Tunjung; Andri Kenti Gayatina (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
The golden age refers to a crucial period in a child's growth and development. Optimal child development is essential for children to be better prepared for school. A preliminary study revealed that 12 of the 18 children at Imanuel Christian Kindergarten experience suspect based on Denver II examination. Appropriate efforts from healthcare professionals are needed to anticipate further problems resulting from delays. This Community Service (PkM) aimed to increase parental knowledge about age-appropriate stimulation, healthy sleep, and omega-3, and to optimize the development of preschool children through snakes and ladders play therapy. Parents received counseling on the theme